INFLUENCE OF SMOKING BAN IN EATERIES ON SMOKING ATTITUDES AMONG ADULT SMOKERS IN KLANG VALLEY MALAYSIA - Jinat Ahmed; Mathialagan AG; Nazmul Hasan (Malaysian Journal of Public Health Medicine, 2020)
The objective of this study was to determine the effect of smoking ban in eateries on smoking behaviors and intention to quit smoking among adult smokers in Klang Valley. A validated questionnaire was utilized for this study whereby three variables of the study (socio-demographic characteristics, smokers attitude, and intention to quit smoking) were measured. The structured questionnaire contained closed ended questions where present of dichotomous(yes/no), multiple choice questions and 7-point likert scale questions. 600 questionnaires were distributed to target respondents in eateries of Klang Valley. The inclusion criteria were local citizen of Malaysia, those who gave consent to take part in the study, literate in English, smokers aged 18 years old and above. The data were analyzed utilizing SPSS software version 21.0. There were 504 completed and usable responses received, which represented an 84% response rate. Majority of smokers in Klang Valley were male which constituted around 78.2% of the respondents. Manufactured cigarette, 75.2% was the most preferred type of nicotine among smokers. Smokers attitude and social support with a smoking ban in restaurants and eateries was significantly associated with intention to quit smoking. 73.8% of smokers agree that the smoking ban in eateries and restaurants have reduced their daily smoking frequency and 58.3% of smokers agreed that the nationwide smoking ban at eateries and public places aspire them to quit smoking.Smoking ban is beneficial to help reduce prevalence of smoking among smokers that in turn helps to reduce secondary smoking and burden of non-communicable diseases in the long run. Though only a little over half of the respondents claimed that the ban inspires them to quit smoking, this is a positive start as the ban was just introduced. When effectively implemented, they are seen as an important element of policy to support behavior change in favor of a healthy lifestyle. The Ministry of Health should push forward with the ban on public smoking as soon as possible. The ban should be in tandem with efforts to help smokers quit. Implementing this scheme nationwide would be a remunerative move to help strive for a better health and cleaner environment for this country.